PENYELESAIAN PERKARA PIDANA ANAK SECARA ADAT LAMPUNG MEGOW PAK TULANG BAWANG DALAM RANGKA RESTORATIVE JUSTICE - Hendri Pratama (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
The completion of the juvenile criminal case in restorative justice can be done in a various way, one of the completion is using Megow Pak Tulang Bawang custom. The results of this research, in the completion process of juvenile criminal case using Megow Pak Tulang Bawang Lampung Custom, there are several stages and the completion of juvenile criminal case using Megow Pak Tulang Bawang Lampung Custom has been suitable with restorative justice principle because in the settlement, involving all stakeholder and using penal mediation that was form of restorative justice. There are several reason the completion of the juvenile criminal case using Megow Pak Tulang Bawang custom rarely used, that are: the society is not homogenous anymore, there are no strict rules that recognize the unity of customary law, and sometimes the authority is taken by law enforcement officers contrary to customary law of Megow Pak. Suggestions for this research is the completion of juvenile criminal case using Megow Pak Tulang Bawang Lampung custom can be taken as consideration for the law enforcement officers in Juvenile criminal case completion and also as well as consideration in formulating the new rules (Ius constituendum). Keywords: Juvenile Criminal Cases, Lampung Costum, Restorative Justice.